Challenges to wastewater aquaculture: a case study of traditional and emerging contaminant concentrations in African catfish [Abstract only] - Asem-Hiablie, S.; Yeboah-Agyepong, M.; Amoah, Philip; Church, C.D.; Shappell, N.; Schoenfuss, H.L.; Aikins, S.; Agbo, N.W.; Drechsel, Pay (2014)
Municipal wastewater-fed aquaculture promotes efficient water use, however, the potential effects of wastewater-borne traditional and emerging contaminants on fish and human health are potential challenges. The pathogen and heavy metal accumulation in fish tissue and serum estrogenicity and biological effects of wastewater-borne estrogens were assessed in African catfish (Clarias gariepinus) raised in a wastewater stabilization ponds (WSP) of a functioning municipal wastewater treatment plant and reference ponds (RP) unimpacted by wastewater, located in Ghana (West Africa). Preliminary results showed that significantly higher levels (2-3 log units) of pathogen (E. coli) contamination were detected in the gut and skin of fish from the WSP than the reference ponds (p = 0.05). Furthermore, the levels of heavy metals found in fish tissue were below the expected daily nutritional requirement (1-2 mg) for humans and poses insignificant toxicological risks. The mean estrogen concentrations were higher in the wastewater ponds than the reference and fish serum assayed by E-SCREEN showed significantly higher estrogenicity in female vs. male catfish in the RP compared to the WSP (p = 0.05). Histological examination of liver and gonad tissues showed no apparent signs of intersex or pathology. These studies showed that catfish cultivated at the study sites were safe for human consumption, however, precautions such as depuration and effective processing methods including grilling and smoking prior to consumption are recommended to reduce pathogen loads. In terms of fish health, biological metrics in this study suggest that aquacultural use of adequately treated municipal wastewater had minimal estrogenic effects on African catfish. Investigation of other growth and reproduction-modulating compounds (e.g. androgens) are needed.